Micro-nano light trapping structure and two-dimensional material integrated photoelectric sensor and preparation method and application thereof
By integrating micro-nano trap light structure and two-dimensional materials in photoelectric sensors, the problem of poor performance of traditional photodetectors in wide spectrum and high sensitivity detection is solved, and higher photoelectric conversion efficiency and sensitivity are achieved.
Patent Information
- Application Number
- CN202510075223.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional silicon-based photodetectors perform poorly in wide-spectrum and high-sensitivity detection, and the photoelectric conversion efficiency of a single material is low, making it difficult to effectively detect weak light signals.
A photoelectric sensor is used to integrate micro-nano trap light structures with two-dimensional materials (such as molybdenum disulfide or platinum ditin) to optimize the combination of light convergence, transparent upper electrodes and two-dimensional material layers through the stacked structure to form an efficient photoelectric conversion device.
It improves the sensitivity and spectral response range of the photoelectric sensor, enhances the photoelectric conversion efficiency, and is suitable for applications such as high-sensitive detection imaging and low-light night vision.
Smart Images

Figure CN119922996A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photoelectric sensors, and in particular relates to a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of optoelectronic technology, the demand for high-performance photodetectors in the fields of communications, environmental monitoring, medical diagnosis, security monitoring, etc. is growing. Among them, high-sensitivity photodetectors can effectively improve the detection efficiency of optical signals and meet the detection requirements in weak light environments. Traditional silicon-based photodetectors have limited detection capabilities for weak light signals due to their planar structure, low photoelectric conversion efficiency of single materials, and limited application in wide spectrum detection and high-sensitivity detection.
[0003] In recent years, transition metal dichalcogenides have attracted extensive attention from researchers due to their unique two-dimensional layered structure, wide spectrum absorption ability and excellent optoelectronic properties. As a typical TMD material, molybdenum disulfide (MoS2) has a direct band gap (~1.8 eV) and high carrier mobility, which can achieve wide spectrum detection from ultraviolet to near infrared. In addition, MoS2 has good interface compatibility with silicon, which is convenient for the preparation of heterojunction devices. However, when using planar MoS2 thin film materials alone, its light absorption efficiency is low, which limits the photoelectric conversion performance of the device.
[0004] Therefore, how to provide a high-sensitivity, wide-spectrum photoelectric detector to meet the needs of practical applications by optimizing material structure and process parameters is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material, and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material, comprising a light convergence layer, a transparent upper electrode layer, a two-dimensional material layer, a micro-nano light trapping structure layer, a lower electrode layer and a readout circuit layer stacked in sequence;
[0008] Wherein, the two-dimensional material layer is deposited and wrapped on the surface of the micro-nano light trapping structure layer;
[0009] The transparent upper electrode layer is partially wrapped around the surface of the two-dimensional material layer, and is partially overlapped between the two structures.
[0010] Beneficial effect: The transparent upper electrode layer in the present invention forms a conformal coating with the micro-nano light-trapping structure coated with the two-dimensional material. The transparent upper electrode material is in close contact with the two-dimensional material, which is beneficial to the collection of electrons and avoids the difficulty of the transparent upper electrode layer built on the upper surface to collect electrons on the side walls and bottom of the structure, thereby increasing the probability of electron recombination and reducing the sensitivity of the device.
[0011] Preferably, the two-dimensional material layer is molybdenum disulfide or platinum ditinide.
[0012] Beneficial effects: Two-dimensional materials are layered thin film materials, which are beneficial to forming continuous thin films on the surface of three-dimensional micro-nano light-trapping structures. On the other hand, molybdenum disulfide or platinum ditinide in two-dimensional materials has a wide spectral response, which is more beneficial to the preparation of high-sensitivity detectors.
[0013] Preferably, the transparent upper electrode layer is a metal nanowire film and / or an ITO film.
[0014] More preferably, the metal nanowires in the metal nanowire film are silver nanowires or copper nanowires.
[0015] Beneficial effects: Metal nanowires have attracted much attention as a wide-spectrum transparent conductive electrode material, and their unique properties make them an important breakthrough in the field of high-transmittance and high-conductivity materials. First of all, the excellent conductivity of metal nanowires is one of their notable characteristics. Using nano-level metal materials such as silver and copper, metal nanowires form a structure arranged vertically and horizontally, thereby obtaining a highly conductive film. Secondly, metal nanowires show high transparency over a wide spectrum. Its diameter is usually between tens of nanometers and hundreds of nanometers, and the conductive network has less scattering and absorption of light, which makes it perform well in transparent electrodes. This also provides an ideal choice for electronic devices that require transparency, such as liquid crystal displays and touch screens, and transparent upper electrodes for wide-spectrum photodetectors.
[0016] Preferably, the micro-nano light trapping structure layer is a three-dimensional micrometer-nanoscale structure substrate with high light absorption, including any one of a columnar structure, a groove structure, a hemispherical structure, a pointed cone structure, a hole structure or a step structure, or a combination of at least two thereof.
[0017] Beneficial effects: The three-dimensional micrometer-scale nanometer-scale structure in the present invention has theories such as equivalent medium theory, guided mode resonance theory, light field coupling effect, slow light effect, etc., which further promotes the light absorption ability, improves the weak light detection efficiency, and improves the sensitivity of the device.
[0018] Preferably, the light convergence layer is a photoresist prepared by using photolithography technology and hot-melt technology.
[0019] Preferably, the lower electrode layer is prepared by evaporation.
[0020] Beneficial effects: The light convergence layer in the present invention is beneficial for converging light from different directions on the surface of the device structure, further improving the light utilization rate. On the other hand, the light convergence layer isolates the air from the device, reducing the impact of adverse factors such as air and water molecules in the environment on the device.
[0021] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide comprises the following steps:
[0022] The wind-controlled induced deposition method is used to deposit two-dimensional materials on the surface of the micro-nano light-trapping structure of the substrate, and then a three-dimensional transparent upper electrode layer is built on the surface of the micro-nano light-trapping structure coated with the two-dimensional material. Finally, a light-converging layer is prepared on the surface of the transparent upper electrode, and at the same time, a lower electrode is prepared on the other end surface of the substrate and bonded to the readout circuit for integration.
[0023] Preferably, the substrate is obtained by preparing a vertically ordered high light absorption micro-nano light trapping structure layer on one end surface of a single crystal silicon wafer by photolithography.
[0024] Preferably, during the wind-controlled induced deposition method, the vacuum degree is less than -4 -4 pa, the temperature is 600-1000°C, the atmosphere is a mixture of argon and hydrogen in a volume ratio of (4-5):1, and the flow rate is 10-80sccm.
[0025] Beneficial effect: After the wind controller of the present invention is turned on, the fan in the wind controller rotates with the steering gear. Under the action of the fan, the airflow flows out through the cyclone holes, and the wind controller adjusts the flow rate by controlling the speed of the fan. The fan rotates under the control of the steering gear, and the airflow flows out through the cyclone holes, generating a cyclone effect. According to the experimental requirements, the speed of the airflow can be accurately controlled by the speed of the fan and the adjustment of the steering gear to ensure that the reactants can enter the micro-nano light-trapping structure evenly and efficiently. The cyclone effect generated by the rotation of the fan in the wind controller makes the movement of the airflow present a rotating characteristic. This cyclone airflow helps to enhance the diffusion and transmission efficiency of the gas, so that the reactants can pass through the micro-nano light-trapping structure more quickly. The formation of the cyclone not only accelerates the entry of the reactants, but also enhances the uniformity and rate of the reaction by increasing the turbulence of the gas flow. Through the cyclone airflow, the wind controller can bring the sublimated sulfur into the micro-nano light-trapping structure area to ensure that the metal molybdenum film fully reacts with the sublimated sulfur in a high temperature environment to generate molybdenum disulfide. The air velocity and directionality of the cyclone ensure uniform distribution of the precursor, making the reaction more efficient and consistent. The fan of the wind controller can not only control the flow rate of the airflow through the rotation of the servo, but also adjust the directionality of the airflow, thereby accurately controlling how the airflow enters the reaction area. This adjustability enables the system to optimize the reaction environment according to actual needs and ensure the accuracy and repeatability of the reaction conditions.
[0026] Preferably, the transparent upper electrode layer is prepared by ultrasonic spin coating. Taking silver nanowires as an example, the preparation steps are as follows: immerse the micro-nano light-trapping structure coated with two-dimensional materials in a 4mg / ml silver nanowire ethanol solution, perform ultrasound at a power of 20W for 8s, immediately put it into a spin coater after the ultrasound ends, and spin coat it at a speed of 2500rmp for 30s, so that the silver nanowires are wrapped on the surface of the micro-nano light-trapping structure coated with two-dimensional materials, and then drop 6mg / ml silver nanowire ethanol solution on the surface of the substrate, and spin coat it at a speed of 1500rmp for 30s to form a film, that is, a layer of mesh silver nanowire film is built on the upper surface of the micro-nano light-trapping structure coated with two-dimensional materials, and a three-dimensional transparent upper electrode layer is obtained.
[0027] Preferably, the wind-controlled induced deposition is carried out in a tubular furnace, wherein the interior of the tubular furnace comprises a precursor reaction boat, a small molecule filter screen, a substrate carrier, an airflow blocking sheet, a thin film growth substrate and a wind controller arranged at intervals.
[0028] Beneficial effects: The wind-controlled induced deposition adopted in the present invention is beneficial for the precursor to enter the gap of the micro-nano light-trapping structure and be evenly distributed around the micro-nano light-trapping structure. After the high-temperature reaction, the material obtained by the reaction is close to the top, side wall and bottom of the micro-nano light-trapping structure.
[0029] A photoelectric sensor integrating a micro-nano light-trapping structure and a two-dimensional material is used in the fields of high-sensitivity detection imaging and low-light-level night vision.
[0030] Beneficial effects: The micro-nano light-trapping structure at the level of hundreds of nanometers can form a resonant cavity, reduce light reflection, promote light absorption, and form a heterojunction with two-dimensional materials to promote the separation of electrons and holes, improve photoelectric conversion efficiency, and enhance detector sensitivity.
[0031] Compared with the prior art, the present invention has the following advantages and technical effects:
[0032] The photoelectric sensor integrated with the micro-nano light trapping structure and the two-dimensional material provided by the present invention has low power consumption and high integration, can achieve high photoelectric conversion efficiency, and the preparation method is simple and efficient, and can achieve the coating and deposition of the two-dimensional material on the surface of the wafer-level micro-nano light trapping structure, which is convenient for industrial promotion and application. At the same time, the coated silver nanoparticles and the constructed silver nanowires provide excellent paths for the transmission and collection of electrons, further improving the sensitivity of the device. The obtained optical sensor can be widely used in aviation, aerospace, military industry, security and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0034] Figure 1 This is a schematic diagram of the wind-controlled induced deposition principle of two-dimensional materials in Example 1 of the present invention;
[0035] Figure 2 This is a flow chart of depositing two-dimensional materials on the surface of the micro-nano light trapping structure in Example 1 of the present invention;
[0036] Figure 3 The wind-controlled induced deposition growth device for two-dimensional materials in Example 1 of the present invention;
[0037] The reference numerals are: 7 front air inlet, 8 quartz tube, 9 precursor reaction boat, 10 reaction precursor, 11 small molecule filter screen, 12 air flow blocking sheet, 13 substrate carrier, 14 film growth substrate, 15 wind controller and 16 rear air outlet;
[0038] Figure 4 This is a schematic diagram of a wind controller in Embodiment 1 of the present invention;
[0039] The numbers are: 17 steering gear, 18 fan, 19 cyclone air hole;
[0040] Figure 5 Schematic diagram of the structure of the photoelectric sensor integrating the micro-nano light trapping structure and the two-dimensional material in Example 1 of the present invention; wherein 1 is a light convergence layer, 2 is a transparent upper electrode layer, 3 is a two-dimensional material layer, 4 is a micro-nano light trapping structure layer, 5 is a lower electrode layer, and 6 is a readout circuit layer;
[0041] Figure 6 This is a SEM image of the surface of the micro-nano light trapping structure coated with molybdenum disulfide in Example 1 of the present invention;
[0042] Figure 7 This is a Raman image of the surface of the micro-nano light trapping structure coated with molybdenum disulfide in Example 1 of the present invention;
[0043] Figure 8 This is a diagram of the external quantum efficiency of the device in Example 1 of the present invention;
[0044] Fig. 9 The silicon nano spikes in Example 2 of the present invention;
[0045] Fig.10 This is a graph showing the test results of the silicon nanorod array using a UV-visible-near infrared spectrophotometer;
[0046] Fig.11 The surface of the micro-nano light trapping structure in Example 1 of the present invention is coated with molybdenum disulfide at 1-10 -3 Light response diagram under low light conditions of lx. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0050] The method for preparing the silicon nanorod array comprises the following steps:
[0051] 1. Material Preparation
[0052] Select high-quality single-crystal silicon wafers, usually (100) crystal orientation, n-type or p-type, and select the doping type as needed. Select a suitable positive photoresist (such as AZ5214E) or negative photoresist (such as SU-8), which is determined according to the etching process requirements. Use acetone, isopropyl alcohol (IPA) and deionized water (DI water) to ultrasonically clean the silicon wafer to ensure that there are no organic pollutants on the surface. Use hydrofluoric acid (HF, mass concentration is 5%-10%) solution to remove the natural oxide layer on the surface of the silicon wafer, and then use nitrogen to blow dry the surface of the silicon wafer.
[0053] 2. Coating photoresist
[0054] Pre-bake the silicon wafer to 90-100°C and keep it for 1-2 minutes, then adjust the speed of photoresist coating to 3000-4000rpm for 30-60s according to the photoresist thickness requirement, and control the photoresist thickness to 0.5-2μm.
[0055] 3. Photolithography
[0056] Use the designed mask to ensure that the pattern is aligned with the silicon wafer surface and expose it under ultraviolet (UV) or deep ultraviolet (DUV) conditions. The wavelength of ultraviolet (UV) or deep ultraviolet (DUV) is 365nm or 248nm, and the exposure energy is 100-150mJ / cm 2 (Optimized according to the photoresist type), then develop with AZ series developer (AZ400K or diluted alkali solution) for 30-60s until the pattern is clearly visible. After development, bake at 110-120℃ for 1 minute.
[0057] 4. Etching to Prepare Silicon Nanopillar Arrays
[0058] In a mixed atmosphere of SF6 (sulfur hexafluoride) and O2, using photoresist directly as a mask (suitable for low aspect ratio structures) or using silicon oxide (SiO2) or a metal mask to improve etching resistance, using reactive ion etching (RIE) or deep reactive ion etching (DRIE), anisotropic etching method, etching at a power of 100-200W for 5-20 minutes to obtain a nano-pillar structure with a high aspect ratio. Among them, the gas flow rate is: SF6 (40-60sccm), O2 (5-10sccm); the chamber pressure is: 10-50mTorr. Then use acetone solution or O2 plasma to remove the photoresist residue, and the silicon nano-pillar array is obtained.
[0059] like Fig.10 As shown, the etched silicon nanorod array was tested by a UV-visible-near-infrared spectrophotometer, and the average external quantum efficiency was greater than 90% in the wavelength range of 380-1100 nm.
[0060] The tubular furnace structure used in the present invention is as follows Figure 3 As shown, it includes 7 front air inlets, 8, quartz tube, 9 precursor reaction boat, 10 reaction precursor, 11 small molecule filter screen, 12 airflow blocking sheet, 13 substrate carrier, 14 thin film growth substrate, 15 wind controller and 16 rear air outlet arranged at intervals. The reaction precursor 10 is located on the side of the precursor reaction boat 9 close to the small molecule filter screen 11, the small molecule filter screen 11 is used to filter the large particle reaction precursor that is heated and volatilized, the substrate carrier 13 is placed with 12 airflow blocking sheet and 14 thin film growth substrate in front and behind, and the side of the thin film growth substrate 14 with structure is close to the wind controller 15.
[0061] The structure of the wind controller 15 used in the present invention is as follows Figure 4 As shown, the cyclone flow devices are arranged in an array shape inside, and the cyclone flow devices are composed of 17 steering gears, 18 fans, and 19 cyclone air holes.
[0062] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0063] Example 1
[0064] A photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide, wherein a molybdenum disulfide (MoS2) film is formed on the surface of a silicon nanocolumn, and specifically comprises a light-converging layer 1, a transparent upper electrode layer 2, a two-dimensional material layer 3, a micro-nano light trapping structure layer 4, a lower electrode layer 5 and a readout circuit layer 6 stacked in sequence;
[0065] Wherein, the two-dimensional material layer 3 is deposited on the surface of the micro-nano light trapping structure layer 4;
[0066] The transparent upper electrode layer 2 is partially wrapped on the surface of the two-dimensional material layer 3, and the remaining part is built on the top of the micro-nano light trapping structure;
[0067] The two-dimensional material layer 3 is a molybdenum disulfide film.
[0068] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide comprises the following steps:
[0069] (1) Deposition of metallic molybdenum on the surface of silicon nanorods
[0070] A silicon nanorod array with a diameter of 500 nm, a height of 800 nm, and a spacing of 500 nm was selected as the substrate. The size was 10 mm*10 mm. Metal molybdenum was deposited on the substrate surface by magnetron sputtering. The vacuum degree of the magnetron sputtering chamber was reduced to 2.0×10 -5 Pa, the Ar gas flow rate was adjusted to 20 sccm, the Mo target power was 5 W, and the sputtering time was 13 s, so that metallic molybdenum was deposited on the top, bottom and sidewall of the three-dimensional silicon nanorod array.
[0071] (2) CVD metal molybdenum sulfide forms a molybdenum disulfide film on the surface of silicon nanorods
[0072] like Figure 2 As shown, the substrate with the metal molybdenum film deposited thereon and the sublimated sulfur powder are placed in a vacuum tube furnace annealing system, as shown in FIG. Figure 3 As shown, the substrate deposited with the metal molybdenum film is placed inverted with the side with the metal film facing the wind controller, and the vacuum is drawn. A mixed gas with a total flow rate of 100 sccm is introduced, and the main annealing furnace is turned on and the temperature is raised to 680°C. Then, the substrate deposited with the metal molybdenum film is placed in the center of the temperature zone, and the preheating furnace is turned on to heat the sublimated sulfur, and the total flow rate of the mixed gas is reduced to 25 sccm, and the vacuum degree is =0.1Pa; in the mixed gas, the flow ratio of argon and hydrogen is 4:1; during annealing and sulfur sublimation, the heating rates are 2°C / min and 15°C / min, respectively.
[0073] Turn on the wind controller, such as Figure 4 As shown in the figure, the fan in the wind controller rotates with the steering gear. Under the action of the fan, the wind flows out through the cyclone holes. The wind controller adjusts the flow rate by controlling the speed of the fan. The fan rotates under the control of the steering gear, and the airflow flows out through the cyclone holes, producing a cyclone effect. According to the experimental requirements, the speed of the airflow can be precisely controlled by adjusting the fan speed and the steering gear to ensure that the reactants can enter the micro-nano light trapping structure evenly and efficiently. Figure 1 As shown in FIG. 1 , the cyclone effect generated by the rotation of the fan in the wind controller makes the airflow present a rotating characteristic. The temperature is maintained at 680°C for 10 minutes under the regulation of the wind controller, and then the main annealing furnace is removed to obtain a micro-nano light-trapping structure coated with molybdenum disulfide. The SEM photo of the structure is shown in FIG. Figure 6As shown in the figure, it can be seen that the two-dimensional MoS2 film is evenly coated on the surface of the columnar micro-nano light trapping structure. Although some crystals are precipitated, the overall film quality is high. Figure 7 ) It can be seen that the prepared molybdenum disulfide is a few-layer and has good crystallinity. The average external quantum efficiency exceeds 70%, proving its high sensitivity and is expected to be applied in the field of high-sensitivity detection imaging. Fig.11 It can be seen that the detector is 1-10 -3 It has good response characteristics under low-light conditions of lx and is expected to be applied in the field of low-light night vision.
[0074] (3) Preparation of three-dimensional transparent upper electrode layer
[0075] A wide-spectrum transparent upper electrode is prepared on the material obtained in step (2), and a mesh three-dimensional conformal coating structure is prepared on the upper surface of the micro-nano light-trapping structure coated with the two-dimensional material by using an ultrasonic spin coating method. The micro-nano light-trapping structure coated with the two-dimensional material obtained in step (2) is immersed in a 4 mg / ml silver nanowire ethanol solution, and ultrasonicated at a power of 20 W for 8 seconds. After the ultrasonication, it is immediately placed in a spin coater and spin-coated at a speed of 2500 rpm for 30 seconds, so that the silver nanowires are wrapped around the surface of the micro-nano light-trapping structure coated with the two-dimensional material. Then, a 6 mg / ml silver nanowire ethanol solution is dropped on the upper surface of the micro-nano light-trapping structure coated with the two-dimensional material and the silver nanowires, and spin-coated at a speed of 1500 rpm for 30 seconds to form a film, that is, a mesh silver nanowire film is built on the upper surface of the micro-nano light-trapping structure coated with the two-dimensional material, and a three-dimensional transparent upper electrode layer is obtained.
[0076] (4) Fabrication of photoelectric sensors integrating micro-nano light trapping structures with two-dimensional materials
[0077] Using photoresist as a raw material, a hemispherical lens is prepared on the silver nanowire film obtained in step (3) by using photolithography technology and hot melt technology to obtain a light convergence layer to converge light from different directions onto the surface of the photosensitive material, specifically comprising the following steps:
[0078] The composite base of the silver nanowire film was spin-coated with photoresist at a speed of 2800 rpm for 50 seconds, then baked at 100 ° C for 2.5 minutes, and then reported at 365nm (ultraviolet light) for 30 seconds, wherein the exposure dose was 200mJ / cm 2 , then develop for 90 seconds, heat treat the developed sample at 120°C for 2 minutes, use an optical microscope to check the shape and uniformity of the microlens, adjust the thermal reflow parameters according to the needs, and bake at 180°C for 12 minutes to improve the mechanical strength and chemical resistance of the photoresist, and then use oxygen plasma to treat the surface of the microlens to improve the optical performance and obtain a light convergence layer;
[0079] The lower electrode layer is prepared by evaporation and bonded with the readout circuit layer to complete the preparation of the photoelectric sensor integrating the micro-nano light trapping structure and the two-dimensional material. The device structure is shown in Figure 5. The external quantum efficiency of the device tested by the semiconductor tester is shown in Figure 5. Figure 7 As shown by Figure 7 It can be seen that the average external quantum efficiency of the device is about 80%, which is due to the combined effect of the micro-nano light trapping structure, the two-dimensional material coated on the surface, the transparent upper electrode and the light-converging layer.
[0080] Example 2
[0081] A photoelectric sensor integrating a micro-nano light trapping structure and platinum tin oxide. In this embodiment, a platinum tin oxide (PtSe2) film is formed on the surface of a silicon nano spike, and specifically includes a light convergence layer, a transparent upper electrode layer, a two-dimensional material layer, a micro-nano light trapping structure layer, a lower electrode layer and a readout circuit layer stacked in sequence;
[0082] Among them, a two-dimensional material layer is deposited on the surface of the micro-nano light trapping structure layer;
[0083] The transparent upper electrode layer is partially wrapped around the surface of the two-dimensional material layer;
[0084] The two-dimensional material layer is a platinum tin dioxide (PtSe2) film.
[0085] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide, which is different from that of Example 1 in that steps (1) and (2) include the following steps:
[0086] (1) Deposition of metallic molybdenum on the surface of silicon nanorods
[0087] A silicon nanospike array with a bottom diameter of 100 nm, a height of 500 nm, and a spacing of 500 nm was selected as the substrate. Figure 8 As shown, the size is 10mm*10mm. Metal platinum is deposited on the substrate surface by magnetron sputtering. The vacuum degree of the magnetron sputtering chamber is reduced to 2.0×10 -5 Below Pa, the Ar gas flow rate was adjusted to 20 sccm, the Pt target power was 8 W, and the sputtering time was 10 s, so that metal platinum was deposited on the bottom and sidewalls of the three-dimensional silicon nanospike array.
[0088] (2) CVD platinum tin oxide forms platinum ditin oxide thin film on the surface of silicon nanospikes
[0089] The substrate with the deposited metal platinum film and the sublimated tin powder are placed in a vacuum tube furnace annealing system, such as Figure 3As shown, the substrate deposited with the metal platinum film is placed inverted, with the side with the metal film facing the wind controller, and evacuated. A mixed gas with a total flow rate of 100 sccm is introduced, and the main annealing furnace is turned on and the temperature is raised to 380°C. Then, the substrate deposited with the metal platinum film is placed in the center of the temperature zone, and the preheating furnace is turned on to heat the sublimated tin, and the total flow rate of the mixed gas is reduced to 25 sccm, and the vacuum degree is =0.1Pa; in the mixed gas, the flow ratio of argon and hydrogen is 5:1; during annealing and tin sublimation, the heating rates are 2°C / min and 15°C / min, respectively.
[0090] Turn on the wind controller, such as Figure 4 As shown in the figure, the fan in the wind controller rotates with the steering gear. Under the action of the fan, the wind flows out through the cyclone holes. The wind controller adjusts the flow rate by controlling the speed of the fan. The fan rotates under the control of the steering gear, and the airflow flows out through the cyclone holes, producing a cyclone effect. According to the experimental requirements, the speed of the airflow can be precisely controlled by adjusting the fan speed and the steering gear to ensure that the reactants can enter the micro-nano light trapping structure evenly and efficiently. Figure 1 As shown, through the cyclonic airflow, the wind controller can bring the sublimated sulfur into the micro-nano light trapping structure area, ensuring that the metal molybdenum film fully reacts with the sublimated sulfur in a high-temperature environment to generate platinum ditin. The temperature is maintained at 380°C for 8 minutes under the regulation of the wind controller, and then the main annealing furnace is removed to obtain a micro-nano light trapping structure coated with a two-dimensional material.
[0091] The remaining process steps and parameters are the same as those in Example 1.
[0092] Example 3
[0093] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material, which is different from that of Example 1 in that the method for preparing a three-dimensionally constructed transparent upper electrode layer in step (3) comprises the following steps:
[0094] (3) A wide-spectrum transparent upper electrode is prepared using indium tin oxide (ITO) on the material obtained in step (2). First, an ITO film is sputtered using a magnetron sputtering method with a DC of 50 W and a time of 500 s, so that the ITO film is wrapped around the surface of the micro-nano light trapping structure coated with the two-dimensional material. At the same time, a 6 mg / ml silver nanowire ethanol solution is dropped on the surface of the substrate and spin-coated at a speed of 1500 rpm for 30 s to obtain a three-dimensional transparent upper electrode layer.
[0095] The remaining process steps and parameters are the same as those in Example 1.
[0096] Comparative Example 1
[0097] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide, which is different from that in Example 1, in step (2), a wind-controlled induced deposition method is not used to assist, but a single chemical vapor deposition method is used to deposit molybdenum disulfide, specifically comprising the following steps:
[0098] First, a silicon nanorod array is selected and ultrasonically cleaned in deionized water (DI water), acetone and ethanol in sequence to remove surface contaminants. Soak in a 2% dilute hydrofluoric acid solution for 1 minute to remove the oxide layer, then rinse with DI water and blow dry with nitrogen. Prepare solid precursors: Use a high-purity molybdenum source (such as ammonium molybdate or MoO3 powder) and sulfur powder. Place the molybdenum source in the high-temperature zone of the CVD system and the sulfur powder in the low-temperature zone. Place the treated substrate in the downstream area of the molybdenum source, parallel to the direction of the gas flow, to ensure that MoS2 is evenly deposited on the substrate surface. Use high-purity argon as the carrier gas with a flow rate of 60sccm. Heat to 750°C and keep the reaction for 45 minutes. Keep the sulfur powder at 212°C in the low-temperature zone to generate sulfur vapor. After the reaction is completed, naturally cool to room temperature.
[0099] The remaining process steps and parameters are the same as those in Example 1.
[0100] Comparative Example 2
[0101] A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and molybdenum disulfide, which is different from that in Example 1, an extremely thin metal is used to prepare a wide-spectrum transparent upper electrode in step (3), and specifically comprises the following steps:
[0102] Place the micro-nano light trapping structure substrate sample coated with two-dimensional materials on the sample stage of the evaporator to ensure that the vacuum environment reaches 10 -6 Torr or less to avoid interference from impurities. During the deposition process, the electron beam or heat source power is controlled at 20-50W to allow the gold target to evaporate slowly, and the deposition rate is set to The film thickness is controlled at 8nm and is monitored in real time by a quartz crystal monitor. The sample temperature is generally kept at room temperature (25°C) and can be heated to 80°C if necessary to improve film uniformity and adhesion. The deposition time is calculated based on the target thickness and rate, for example It takes about 500 seconds to deposit a 10nm film. After the film is deposited, an annealing treatment can be performed, heating at 162°C for 10 minutes under nitrogen or argon protection to optimize the grain structure and film adhesion, thereby preparing a wide-spectrum transparent upper electrode.
[0103] The remaining process steps and parameters are the same as those in Example 1.
[0104] Comparative Example 3
[0105] A method for preparing a photoelectric sensor integrated with a micro-nano light trapping structure and molybdenum disulfide, which is different from Example 1 in that in step (3), an ultrasonic spin coating method is not used to complete the formation of a mesh-like three-dimensional conformal coating structure on the upper surface of the micro-nano light trapping structure coated with a two-dimensional material, but ITO is used to prepare a wide-spectrum transparent upper electrode, which specifically includes the following steps:
[0106] The cleaned silicon nanorod array is loaded into a vacuum chamber, and the sputtering target angle is adjusted to optimize the film coverage. The parameters are as follows: the target material is ITO (In2O3: SnO2, 90:10), the sputtering atmosphere is a mixed atmosphere of argon (Ar) + oxygen (O2), the oxygen volume fraction is 3%, the working pressure is 0.3Pa, the sputtering power is 200W (DC or RF mode), the substrate temperature is room temperature or heated to 180°C, the deposition time is 25 minutes, and the film thickness is controlled within the range of 80nm. In order to improve the crystallinity and conductivity of the ITO film, annealing treatment is carried out in an inert atmosphere at a temperature of 350°C for 12 minutes.
[0107] The remaining process steps and parameters are the same as those in Example 1.
[0108] Technical effect:
[0109] The main disadvantage of Comparative Example 1 compared to the embodiment is that the generated two-dimensional material is difficult to be evenly and extensively coated on the surface of the micro-nano light trapping structure. The main disadvantage of Comparative Examples 2 and 3 compared to the embodiment is that if the deposited upper electrode is thin, although the transmittance is high, it is difficult to form a continuous electrode film on the surface of the entire structure (top, sidewall, bottom), which affects the collection of electrons. If the deposited upper electrode is thick, the electron collection ability of the device is improved, but the number of photons received by the device is affected. In short, too thick or too thin will affect the improvement of the device sensitivity.
[0110] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material, characterized in that: It includes a light-converging layer, a transparent upper electrode layer, a two-dimensional material layer, a micro-nano light-trapping structure layer, a lower electrode layer and a readout circuit layer stacked in sequence; Wherein, the two-dimensional material layer is deposited and wrapped on the surface of the micro-nano light trapping structure layer; The transparent upper electrode layer is partially wrapped around the surface of the two-dimensional material layer, and is partially overlapped between the two structures.
2. The photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 1, characterized in that: The two-dimensional material layer is a molybdenum disulfide layer or a platinum ditinide layer.
3. The photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 1, characterized in that: The transparent upper electrode layer is a metal nanowire film and / or an ITO film.
4. The photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 1, characterized in that: The micro-nano light trapping structure layer is a three-dimensional micron-nano structure substrate with high light absorption, including any one of a columnar structure, a groove structure, a hemispherical structure, a pointed cone structure, a hole structure or a step structure, or a combination of at least two thereof.
5. The photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 1, characterized in that: The light convergence layer is a photoresist prepared by using photolithography technology and hot-melt technology.
6. The photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 1, characterized in that: The lower electrode layer is prepared by using photoresist through evaporation method.
7. A method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: A two-dimensional material layer is deposited on the surface of the micro-nano light-trapping structure layer of the substrate using a wind-controlled induced deposition method, and then a three-dimensional transparent upper electrode layer is built on the surface of the micro-nano light-trapping structure coated with the two-dimensional material. Finally, a light-converging layer is prepared on the surface of the transparent upper electrode layer, and a lower electrode layer is prepared on the other end surface of the substrate, and is bonded and integrated with the readout circuit layer.
8. The method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 7, characterized in that: During the wind control induced deposition method, the vacuum degree is less than -4 -4 pa, the temperature is 600-1000°C, the atmosphere is a mixture of argon and hydrogen in a volume ratio of (4-5):1, and the flow rate is 10-80sccm.
9. The method for preparing a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material according to claim 7, characterized in that: The transparent upper electrode layer is prepared by ultrasonic spin coating.
10. Application of a photoelectric sensor integrating a micro-nano light trapping structure and a two-dimensional material as described in any one of claims 1 to 6 in the fields of high-sensitivity detection imaging and low-light-level night vision.